Harnessing the power of storytelling: A play therapy intervention to reduce disruptive classroom behaviors - Darusman, Mhd. Ricky; Takdir, Annisya Muthmainnah; Hidayati, Diana Savitri (Psychological Research and Intervention, 2024)
Managing classroom behavior is a global challenge, with disruptive actions like talking out of turn and physically disturbing peers undermining both teaching effectiveness and the learning experience. Traditional disciplinary methods often fall short, sometimes exacerbating the very behaviors they aim to curb. This study introduces a novel approach: storytelling-based play therapy, designed to reduce specific disruptive behaviors within the classroom. Focusing on an 8-year-old child identified as frequently disruptive, the intervention involved four consecutive days of 30-minute storytelling sessions, each crafted to enhance social skills, empathy, and self-regulation. The results were compelling a 25% reduction in talking out of turn and a dramatic 62.5% decrease in physical disturbances. These findings suggest that storytelling is not only an engaging and non-punitive strategy but also one that can bring about significant behavioral improvements. While the study's single-subject design limits generalizability, the promising outcomes open the door for further research across diverse educational settings. This research underscores the potential of storytelling as a transformative tool in classroom management, offering educators a creative and effective alternative to conventional disciplinary practices. By fostering a more positive and inclusive environment, storytelling could become a cornerstone of modern behavior management strategies in schools.